1999
DOI: 10.1097/00007890-199908270-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Thymectomy on Tolerance Induction and Cardiac Allograft Vasculopathy in a Miniature Swine Heart/Kidney Transplantation Model1,2

Abstract: Thymic-dependent mechanisms are necessary for the induction of acquired tolerance and prevention of CAV in porcine heart/kidney recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…These data, together with our previous studies demonstrating the necessity of the host thymus for induction of tolerance in this model (4), support the hypothesis that radiosensitive cells derived from the kidney traffic to the thymus by way of the peripheral circulation to induce tolerance to donor antigen in the host. Preliminary studies suggest that the unresponsiveness induced in these recipients may ultimately be mediated by CD4 ϩ CD25 ϩ regulatory T cells (22).…”
Section: Infusion Of Leukapheresis Product From a Tolerant Animal Intsupporting
confidence: 87%
See 1 more Smart Citation
“…These data, together with our previous studies demonstrating the necessity of the host thymus for induction of tolerance in this model (4), support the hypothesis that radiosensitive cells derived from the kidney traffic to the thymus by way of the peripheral circulation to induce tolerance to donor antigen in the host. Preliminary studies suggest that the unresponsiveness induced in these recipients may ultimately be mediated by CD4 ϩ CD25 ϩ regulatory T cells (22).…”
Section: Infusion Of Leukapheresis Product From a Tolerant Animal Intsupporting
confidence: 87%
“…Subsequent studies have been directed toward elucidating the mechanism by which tolerance is induced in such porcine recipients of heart plus kidney allografts and how this acquired tolerance prevents the development of CAV. These studies have included an assessment of the role of antigen load (3) and the demonstration of an important role for the thymus in permitting tolerance to occur (4). In the present study, we tested the hypothesis that cells found in the kidney but not in the heart may be responsible for facilitating the induction of tolerance.…”
Section: Conclusion Radiosensitive Elements In Kidney Allograft Maymentioning
confidence: 92%
“…In a large animal model, it has been shown that thymus-dependent mechanisms facilitate the development of allograft tolerance (25)(26)(27). Rodent studies have demonstrated that donor alloantigen administered peripherally can, under some circumstances, enter the recipient thymus (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that the presence of an intact thymus is required for the development of rapid and stable tolerance in miniature swine (8,23,46). Thus, if the recipient thymus was removed 3 wk before a class I-disparate kidney or heart transplant, tolerance was not obtained (8,24). In the present study, thymectomized recipients were used to determine whether a thymic graft is capable of replacing the effect of the host thymus in permitting the induction of tolerance to a class I-mismatched kidney transplant.…”
Section: Discussionmentioning
confidence: 99%